Regulation, trust, and cronyism in Middle Eastern societies: The simple economics of 'wasta' - Andy Barnett; Bruce Yandle; George S. Naufal (Institute for the Study of Labor (IZA), 2013)
Despite being a fixture of everyday life in the Arab world, wasta, which may be thought of as special influence by members of the same group or tribe, has received little attention from social scientists. Our casual empiricism suggests that wasta is an important determinant of how economic activities are organized and resources are allocated in Middle Eastern societies, yet economists, even those who specialize in work related to the Middle East, have not addressed the issue of wasta. With this paper we provide a modest beginning to filling that void. Specifically, we use the history of wasta, Hayek's concept of extended order and Coase's work on the nature of the firm to draw inferences regarding the existence of wasta and its persistence in Arab societies.
Keywords: D21; K20; N45; 330; cronyism; wasta; firm; Hayek; Coase; Middle East